2012
DOI: 10.1007/s00127-012-0623-5
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality and mental health problems in adolescents from East London: a prospective study

Abstract: This study is concordant with previous observational studies in describing relationships between measures of diet quality and mental health problems in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 21 publications
8
85
1
3
Order By: Relevance
“…However, although healthy dietary habits are known to be mostly associated with physical activity (62) , the present study showed no significant differences between boys and girls in terms of MD adherence level. Several authors have suggested that there is a significant association between unhealthy dietary patterns and poor mental health in children, adolescents and adults, and this is especially true for depression and anxiety (7,(64)(65)(66) . In a recent large national longitudinal survey of Canadians aged 18 years and older, Kingsbury et al (67) suggested that relationships between healthy intake (fruit and vegetables) and depression are complex.…”
Section: Discussionmentioning
confidence: 99%
“…However, although healthy dietary habits are known to be mostly associated with physical activity (62) , the present study showed no significant differences between boys and girls in terms of MD adherence level. Several authors have suggested that there is a significant association between unhealthy dietary patterns and poor mental health in children, adolescents and adults, and this is especially true for depression and anxiety (7,(64)(65)(66) . In a recent large national longitudinal survey of Canadians aged 18 years and older, Kingsbury et al (67) suggested that relationships between healthy intake (fruit and vegetables) and depression are complex.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there was an inverse association between weight gain and increased intake of vegetables, fruits, nuts, yoghurt and whole grains (54) . Studies have found Western-style dietary patterns, high in refined and ultra-processed products such as soft drinks, processed meat products, fast food including hamburgers, pizza and French fries, refined breads and pastries, and sweet and savoury snack foods, to be associated with inferior quality of life, depression and anxiety, and with mental health problems in adolescents (55)(56)(57)(58)(59) . Some authors argue that foods highly refined by industrial processing may be addictive and cause substance abuse-like conditions (60) .…”
Section: Previous Studiesmentioning
confidence: 99%
“…A limited number of prospective studies in adults have reported that diet quality is associated with symptoms of depression over time, [17][18][19] and, to date, only three studies have examined this relationship in adolescents. 12,20,21 Notably, a recent study published in PLoS One by Jacka et al 20 reported that diet quality was associated with mental health symptoms in a large sample of Australia adolescents. In addition, the study reported that changes in diet quality were associated with changes in mental health; improvements in diet quality were associated with higher mental health scores at follow-up but not vice versa.…”
Section: Introductionmentioning
confidence: 96%
“…Of interest, two other adolescent studies did not observe any prospective relationships between diet quality and mental health. 12,21 Additional research is necessary to further understand this relationship and its implications for mental health promotion in this age group.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation